Larvicidal Activity of Hemp Extracts and Cannabidiol against the Yellow Fever Mosquito Aedes aegypti - Erick J. Martínez Rodríguez; P. Larry Phelan; Luis Canas; Nuris Acosta; Harinantenaina L. Rakotondraibe; Peter M. Piermarini (Insects, 2024)
To mitigate pyrethroid resistance in mosquito vectors of emerging and re-emerging human pathogens, there is an urgent need to discover insecticides with novel modes of action. Natural alternatives, such as extracts derived from plants, may serve as substitutes for traditional synthetic insecticides if they prove to be sustainable, cost-effective, and safe for non-target organisms. Hemp (Cannabis sativa) is a sustainable plant known to produce various secondary metabolites with insecticidal properties, including terpenoids and flavonoids. The goal of this study was to assess the larvicidal activity of hemp leaf extract on mosquito larvae from both pyrethroid-susceptible (PS) and pyrethroid-resistant (PR) strains of Aedes aegypti. Another goal was to identify which components of the extract were responsible for any observed larvicidal activity. We found that a methanol extract of hemp leaves induced similar concentration-dependent larvicidal activity against PS (LC50: 4.4 ppm) and PR (LC50: 4.3 ppm) strains within 48 h. Partitioning of the leaf extract between methanol and hexane fractions revealed that full larvicidal activity was restricted to the methanol fraction. Analysis of this fraction by gas chromatography–mass spectrometry and nuclear magnetic resonance showed it to be dominated by cannabidiol (CBD). Larvicidal assays using authentic CBD confirmed this compound was primarily responsible for the toxicity of the hemp leaf extract against both strains. We conclude that hemp leaf extracts and CBD have the potential to serve as viable sources for the development of novel mosquito larvicides.